1999
DOI: 10.1016/s0001-2092(06)62352-1
|View full text |Cite
|
Sign up to set email alerts
|

Snoring and Obstructive Sleep Apnea

Abstract: The most common form of sleep apnea is obstructive sleep apnea (OSA). It is characterized by the cessation of nasal airflow with persistence of ventilatory effort, as shown by paradoxical chest and abdominal movement, and varying degrees of oxygen desaturation. This article describes current methods of diagnosing OSA and available treatment for OSA and snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…They refer to studies which describe a substantial gap between objective and subjective results (postoperative sleep registration and patient satisfaction, respectively) 7–9 . Like other studies, 6,10 we also found that after technically successful performance of UPPP, failures can occur, in the sense of an increase in AHI. In the literature, it seems there are more speculations than explanations for UPPP failure.…”
supporting
confidence: 79%
“…They refer to studies which describe a substantial gap between objective and subjective results (postoperative sleep registration and patient satisfaction, respectively) 7–9 . Like other studies, 6,10 we also found that after technically successful performance of UPPP, failures can occur, in the sense of an increase in AHI. In the literature, it seems there are more speculations than explanations for UPPP failure.…”
supporting
confidence: 79%
“…[1][2][3][4] OSA is well known to result in a number of health consequences: fragmentation of sleep leads to chronic sleep deprivation and daytime somnolence, hence affecting the patients' daily cognitive function and quality of life, increasing incidences of work-related and motor vehicle accidents; cardio-respiratory disturbances lead to elevated risks of complications such as hypertension, pulmonary hypertension, cardiac arrhythmia, myocardial infarction, congestive cardiac failure, and stroke. [1][2][3][4][5][6] Recently, possible ocular manifestations, including optic neuropathy in the form of visual field (VF) defect and disc oedema, normal-tension glaucoma (NTG), pseudotumour cerebri, nonarteritic anterior ischaemic optic neuropathy (NAAION); and anterior segment complications such as floppy eyelid syndrome, upper lid ptosis, lower lid ectropion, blepharochalasis, trichiasis, chronic conjunctivitis, keratoconus, exposure keratopathy, dry eyes, recurrent corneal erosion (RCE), keratitis, and progressive endotheliopathy have aroused ophthalmologists' concern. [7][8][9][10][11][12][13][14][15] However, there are limited evidences in published articles of causal relationship between OSA and the various ocular manifestations, especially in the Chinese locality.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible to hypothesize that oropharyngeal exercises and mobilization exercises of the inspiratory musculature could improve respiratory dynamics during sleep reducing snoring. 49 To the best of our knowledge, this is the first study assessing the efficacy of this novel rehabilitative approach consisting of the combination of myofunctional therapy and myofascial release in mild OSA patients. This rehabilitation protocol required close collaboration among physical and rehabilitative medicine physicians, pulmonology physicians, dentists, and physical therapists.…”
Section: Ta B L Ementioning
confidence: 96%
“…48 Overall, these results are encouraging compared to the scientific literature, also the potential correlation between palatal morphology and OSA. [48][49][50][51] Considering the statistically significant results in the comparison between the groups, the intervention group showed an improvement in terms of reduction of daytime sleepiness, an improvement of the snoring index together with a better oxygen saturation (T-90) versus the control group. Thus, it is possible to hypothesize that oropharyngeal exercises and mobilization exercises of the inspiratory musculature could improve respiratory dynamics during sleep reducing snoring.…”
Section: Ta B L Ementioning
confidence: 99%